Paediatric Intracranial Aneurysms: Long-term Angiographic and Clinical Outcomes in a Contemporary Series - Lu, Junlin; Li, Mingtao; Zhao, Yuanli; Zhao, Yang; Chen, Xiaolin; Zhao, Jizong (Frontiers in Neurology, 2022)
Objective Paediatric aneurysms are rare and difficult to treat. Studies on the long-term angiographic and clinical outcomes conducted within the past decade are lacking. We aimed to investigate the clinical and radiographic outcomes of paediatric aneurysms treated with different strategies in a contemporary series. Methods We performed a retrospective medical record review of paediatric patients examined at our institution between 2011 and 2018. Patient charts were retrospectively reviewed for age, presentation, type and location of the aneurysm, modalities of treatment, complications, and clinical and angiographic outcomes. The rates of aneurysm recurrence and de novo formation were determined. Results We evaluated 61 patients (mean age, 11.6 years; 23 females, 38 males) with 69 intracranial aneurysms. Their presentations included headache, neurological deficits, aneurysmal subarachnoid haemorrhage, incidental aneurysm, and traumatic subarachnoid haemorrhage. Of the aneurysms, 30 (49.2%) were giant. Forty-five (73.8%) patients underwent treatment for their aneurysms, and 16 (26.2%) patients were managed conservatively. The perioperative morbidity rate was 17.8%. There were no deaths. The long-term morbidity rate was 4.6%. The clinical outcomes were favourable in 82.2 and 95.3% at discharge and follow-up, respectively (mean, 41.5 months; range, 1.5–9 years). For treated aneurysms, 2/43 (4.6%) risk of aneurysm recurrence, 1/43 (2.3%) risk of aneurysm bleeding, 1/43 (2.3%) risk of de novo aneurysm formation. The annual bleeding, recurrence, and de novo formation or growth risk were 0.7, 1.4, and 0.7%, respectively. Conclusions In neurovascular centres where microsurgical and endovascular options are available, most children with intracranial aneurysms can be successfully treated with low morbidity and mortality. However, they have higher rates of recurrence and a greater risk of de novo formation or growth than their adult counterparts, which mandates lifelong follow-up.